Effect of Yoga on Cardio Respiratory Parameter in Medical Students (International Journal of Physiology, 2020)
The competition in medical field, unhealthy food and lack of exercise deteriorate the health of student.Yoga is the ancient technique to increase the concentration power, physical and mental well-being. Wehave done randomized control study on medical students between study and control group. The study grouphas practice yoga for 4 weeks whereas the control group hasn’t. In the study group there is significantlyimprovement in cardio-respiratory parameters (p